Implementasi Teknik Equivalence Patitions Pada Aplikasi Perpustakaan Online Menggunakan Metode Black Box - Afifah Yasmin; Dicky Wahyudi; Nabila Eka Rahmayanti; Aries Saifudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
A library application test was run to test the application’s menus, including the master data menu dan the transaction menu. The purpose of testing this software is to find and spot any bugs or irregularities in the application, this application is tested using a black box method and using the equivalence partitioning technique. This technique checks only the types and inputs to the application. The technique used determines whether the entered input is valid. Test results provide a report if there is a discrepancy between the desired result and the test result. Deviations are resolved before the appliaction is distributed to users.